The Application of The Situation, Background, Assessment, Recommendation (SBAR) Method in Nurse Handover Between Shifts in The Hospital - Muhammad Hadi; Tenti Ariyanti; Syamsul Anwar (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: One of the effective communication methods in nursing services is the SBAR (Situation, Background, Assessment, and Recommendation). SBAR is an easy framework for communicating important information between health professionals in the hospital. This study aimed to describe the application of the SBAR method in nurse handovers between shifts. Methods: The research design used a cross-sectional approach. A total of 102 nurses involved in this study were selected by purposive sampling. The research instrument used a questionnaire to evaluate perceptions, knowledge, attitudes, motivation, and application of the SBAR. The bivariate statistical test used Chi-square and the multivariate test used Multiple Logistic Regression. Results: The results showed that the p-value between the perception variables was (0.025 <0.05), knowledge (0.014 <0.05), attitude (0.034 <0.05), and motivation (0.037 <0.05). There was a significant relationship between perception, knowledge, attitude, motivation, and the application of the SBAR method. Conclusion: The dominant factor in applying the SBAR method is the attitude variable. The application of this method may be tested by enhancing the capacity of nurses in the hospital.